Gender Equality and Social Inclusion in Vocational Education and Training - Bhatta, Kushmakar (Journal of Advanced Academic Research, 2017)
Gender Equality and Social Inclusion (GESI) agenda has been used in all and every disciplines of good- governance and development. But a significant portion of the population has largely been unable to participate in the development mainstream owing to their exclusion from the state’s decision-making structures. Among the set goals of Education for All (EFA), National plan of Action (2001-2015), are developed in social inclusion perspectives. The challenges we face today are concerned making the Technical and Vocational Education and Training (TVET) system more effective and need based, more dynamic, inclusive, and responsive to the changes taking place in the world of work. Vocational Education and Training (VET)’s contribution in inclusion will have added benefit to the developing countries as it underpins the fundamental values of society such as equity, justice, nondiscrimination, meaningful participation and social responsibility. This paper presents the case study on status of gender equality and social inclusion in TVET system of Nepal special focusing on Women’s Participation in Non-Traditional Trades/Occupations. The main objective of the article is to explore the inclusion status of women in VET Programs. So, to find out the existing inclusion situation, data from the CTEVT constituted school has been collected and analyzed. It is found that most of the VET programs especially in traditional occupations have high inclusion of the women, whereas poor participation appeared in non-traditional trades. There is still the need to conduct awareness generation activities for the women to maximize their participation in the TVET programs especially in non-traditional occupations. Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 29-39